General hospital costs in England of medical and psychiatric care for patients who self-harm: a retrospective analysis - Tsiachristas, A; McDaid, D; Casey, D; Brand, F; Leal, J; Park, A; Geulayov, G; Hawton, K (Lancet, 2017)
Background: Self-harm is an extremely common reason for hospital presentation. There have, however, been few estimates of the hospital costs of assessing and treating self-harm. Such information is essential for planning services and to help strengthen the case for investment in actions to reduce the frequency and impact of self-harm. Methods: In a retrospective analysis, we estimated hospital resource use and care costs for all presentations for self-harm to the John Radcliffe Hospital in Oxford UK, between April 2013 and March 2014. Episode-related data were provided by the Oxford Monitoring System for Self-harm and linked to financial hospital records to quantify costs. Time and resources allocated to psychosocial assessments were determined through discussion with clinical and managerial staff. Generalised linear models was used to investigate the associations between hospital costs and methods of self-harm. Findings: 1647 self-harm presentations by 1153 patients were recorded in 2013-14. Of these, 1623 (99%) presentations by 1140 patients could be linked to hospital finance records. One hundred and seventy-nine (16%) patients were aged under 18 years. 1150 (70%) presentations were for self-poisoning alone, 367 for self-injury alone (22%) and 130 (8%) for a combination of methods. Psychosocial assessments were made in 75% (1234) of all episodes. The overall mean hospital cost per episode of self-harm was £809. Costs differed significantly between different types of self-harm: self-injury alone £753, self-poisoning alone £806, self-poisoning and self-injury £987 (p<0·005). Costs were mainly associated with the type of health care service contact such as inpatient stay, intensive care and psychosocial assessment. Mean costs of psychosocial assessments were £228 for adults and £392 for under-18 year-olds. Interpretation: If our findings are extrapolated to England, the approximate overall annual cost of general hospital management of self-harm is £162 million per year. More use of psychosocial assessment and other preventive measures, especially for young people and against self-poisoning, could potentially lower future costs at a time of major costs pressures in the NHS.